O papel verde dos jornais : presença do discurso ambiental na imprensa diária do interior do Rio Grande do Sul - Rocha, Mário Eugênio Villas-bôas da (2013)
The environmental theme is both simple and complex. Simple, because of the universal understanding of their key messages, which are not constrained to geography or cultural spaces. Complex, because each unit integrates information webs of interactions increasingly broad whose greatest expression is the life - biodiversity - in the planet that hosts the human species. The study analyze the discourse on the environment present in 17 of the 38 daily newspapers printed in the interior of Rio Grande do Sul that were identified in 2010 when the definition of the sample. We extracted 294 discursive sequences from 2914 pages of 92 editions printed in the week from 1 to 7 April 2011 and they show that, although occuppying editorial spaces for content presentation of local impact, predominantly, these are fragmented expressions of the reality. We discuss the construction of environmental discourse as a journalistic product developed with sensitivity citizen, technical expertise and educational intentionality.